UGT2B7 gene polymorphism and linkage disequilibrium in pediatric epileptic patients and their influence on sodium valproate monotherapy: A cohort study - Adiga, Sachidananda; PB, Nandit; Adiga, Usha; Shenoy, Vijaya (Frontiers in Pharmacology, 2022)
Background: Uridine 5'-diphospho glucuronosyl transferase (UGT) is the main enzyme responsible for the glucuronide conjugation,the principal metabolic pathway of sodium valproate. The objective of the study was to explore if there was an association between the UGT2B7 genetic polymorphism and clinical efficacy and safety in paediatric epileptic patients on sodium valproate monotherapy. Methods and Materials: The cohort study included 100 pediatric epileptic patients aged 2 to 18 years who had been on sodium valproate monotherapy for at least one month. PCR-RFLP was carried out to assess the genetic polymorphism patterns of UGT2B7 (C161T, A268G, G211T). Based on the extent of seizure control throughout the one-year follow-up, clinical outcome was assessed in terms of responders and non-responders. Hepatic, renal, and other lab parameters were assayed to determine safety. The SNPstat web software was used to calculate linkage disequilibrium. Results: Out of 100 patients, CC (38%), CT (43%), TT (19%) pattern was observed in UGT2B7 (C161T) gene, AA(15%), AG(39%), GG(46%) in (A268G) gene and GG(80%), GT(18%), TT(02%) in (G211T) gene. There was no statistical difference in clinical outcome with distinct UGT2B7 genetic polymorphism patterns, according to the findings. With low D' and R2 values, LD between alleles was statistically insignificant. However, the associations of C161T and G211T with treatment response were significant (p=0.014) in determining treatment response. Conclusion: Our findings show that the genetic variation of UGT2B7 had no bearing on the clinical outcome of epilepsy. Gene interactions, on the other hand, had an impact on treatment response.